Identifikasi Pembelajaran Sosial dalam Pengembangan Batik di Kota Pekalongan - Muhammad Indra Hadi Wijaya; Artiningsih Artiningsih; Holi Bina Wijaya; Nofa Martina A.; Bagus Nuari P. (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
Batik as an Indonesian cultural heritage has been recognized by the world in 2009 by UNESCO. This recognition does not fully go hand in hand with the sustainability of batik business and culture in Pekalongan City, especially for business actors in the next generation. This condition is caused by the minimum wage of workers due to the inequality of the subcontracting system in the batik business. This study aims to identify social learning in the batik industry development. The extent to which social learning facilitates the development of batik with regional development. Qualitative methods were carried out for data collection by using in-depth interviews with key business actors in the batik industry chain in the City and Regency of Pekalongan which were selected purposively. The results show that social learning and innovative production processes are still limited with the involvement of the regeneration of young entrepreneurs. The challenges of the batik industry in rural areas depend on how entrepreneurs can enlarge their business net works. This business needs to be more adaptive in utilizing batik not only as an industrial commodity as it is but also processing it creatively as an attraction for Pekalongan City. Keywords: Batik, social learning, sustainability